Effects of Substituting Nb with Ta on Microstructure and Thermal Properties of Novel Biocompatible TiNiNbTa Shape Memory Alloys - Dagdelen, F.; Balci, E.; Qader, I. N.; Aydogdu, Y.; Saydam, S. (Pleiades Publishing Ltd, 2021)
TiNi-based Shape Memory Alloys (SMAs) are important materials that could be used in surgical applications despite the negative effects of the Ni element. In this study, the microstructure, phase transformation temperatures, and biocompatibility of an equiatomic TiNi, TiNiNb, and TiNiNbTa SMAs were examined by SEM-EDS, DSC, and electrochemical corrosive test, respectively. The arc-melting method was utilized to make five samples of Ti50Ni50 and Ti50Ni27Nb(23-x)Tax (x = 0, 1, 3, and 5 at %) SMAs. DSC results showed that the samples have a wide temperature hysteresis for B19' <-> B2 phase transformation; also, the martensite onset temperatures above the room temperature. The XRD and SEM analyses indicated that the matrix phase has a B2 crystal structure at room temperature with beta-Nb phase and friction of the non-dissolved B19' phase. Talium element was the dominant constituent in the dendritic microstructures. Electrochemical corrosion behaviors of the SMAs were investigated in artificial body fluid at room temperature. It was observed that Ni27Ti50Nb20Ta3 with 1.86 x 10(-4) mmpy has the best corrosion rate compared to the other alloys.
Keywords: shape memory allos; Ti-Ni-Nb; phase transformation; biocompatibility; microstructure; corrosion